The Syriac Orthodox Patriarchal register of dues of 1870 - Bcheiry, Iskandar. (Piscataway, NJ)
v, 71 sayfa, 171 sayfa tıpkıbasım
Keywords: “This monograph presents an unpublished historical resource in the form of a register of dues collected for the Syriac Orthodox Patriarchate during the second half of the nineteenth century. Bcheiry provides the original text, an English translation, and an extensive socio-economic study“ -- Yayıncı.